Impact of an Interplatform Collaborative Health Seminar on Reproductive and Psychological Preparedness Among Prospective Brides - Setyowati, Dewi; Kusuma, Ira Nurwahyu; Tricahyanti, Ari; Anindito, Hendrikus Anung; Damayanti, Candra; Sabrina, Aisyah; Kurniawan, Agde Muzaky; Darussalam, Rabhindra Javier Hariri; Arrobbaniy, Najway Azka; Izzah, Iffah Nurul (Rifa'Institute, 2026)
Introduction: Marriage is a critical life transition that influences family quality and long-term well-being. Increasing divorce rates in Indonesia highlight the growing complexity of marital problems, some of which are related to inadequate reproductive health preparedness before marriage. Reproductive health issues, including infertility and undiagnosed conditions, may contribute to marital stress and adverse maternal outcomes. Objective: This study aimed to describe participant satisfaction and perceived benefits of a reproductive health education seminar as part of preconception preparation for prospective couples. Method: A quantitative descriptive survey was conducted among participants of the Serasa Sehatin Seminar: “Prepare Your Future Start Now: Marriage.” Data were collected using an online questionnaire distributed to seminar participants, with responses analyzed using descriptive statistics. Results and Discussion: The evaluation showed that most indicators achieved moderate to high mean scores, indicating positive participant perceptions of content quality and speaker performance. Result and Discussion: The findings suggest that professionally delivered reproductive health education effectively improves understanding of reproductive health and increases awareness of health conditions prior to conception. Conclusions: High-quality reproductive health education is essential in strengthening preconception preparedness and supporting long-term maternal and family well-being.